Performance Analysis on Phase-Encoded OCDMA Communication System in Dispersive Fiber Medium - Chua, C. H.; Abbou, F. M.; Chuah, Hean Teik; Majumder, Satya Prasad (IEEE, 2004)
The performance of an asynchronous phase-encoded optical code-division multiple-access system is evaluated in a dispersive fiber medium. We, derive an approximate analytical expression for the root mean square width of the phase-encoded signal (pseudorandom optical signal with low intensity) propagating in linear dispersive fibers. Bit-error rate analysis of the system is performed in the case of both ordinary single-mode fiber and dispersion-shifted fiber (DSF). The numerical results demonstrate that even though system performance improves due to the smaller width of initial Gaussian optical pulse, the effect from dispersion is higher. Larger code length reduces the effect of dispersion and the use of DSF greatly increases the transmission distance.